2007
DOI: 10.1007/s11897-007-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

The third heart sound for diagnosis of acute heart failure

Abstract: Dyspnea is a common presenting complaint in the emergency department (ED). Rapid identification of heart failure as the etiology leads to early implementation of targeted therapies. Although having only intermediate sensitivity, the S3 is a highly specific finding among older adults with heart failure. Identification of an S3 by routine auscultation can be problematic given the chaotic and noisy ED environment, patient comorbid conditions, and intolerance of ideal positioning for auscultation. Technologies usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Rales may not be present on the pulmonary exam if filling pressures are chronically elevated [ 5 ]. Third heart sounds are heard in fewer than half of patients [ 6 ]. The initial urgent examination may not include careful location of the jugular venous pulsations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rales may not be present on the pulmonary exam if filling pressures are chronically elevated [ 5 ]. Third heart sounds are heard in fewer than half of patients [ 6 ]. The initial urgent examination may not include careful location of the jugular venous pulsations.…”
Section: Discussionmentioning
confidence: 99%
“…Rales may not be present on the pulmonary exam if filling pressures are chronically elevated [5]. ird heart sounds are heard in fewer than half of patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, if coronary heart diseases results in left ventricular dysfunction either acute or chronic leading to a poor ejection fraction. In addition Johnston et al (2007) [45] reported that S4 may be detected in the early phases of acute ischemia and acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with S1, it has characteristics of high tune and short time lasted. S1 and S2 contain important information of cardiac sounds auscultation [3].…”
Section: Introductionmentioning
confidence: 99%